CONCEPÇÃO E MONTAGEM DE UMA UNIDADE DIDÁTICA ANALÓGICA DE APOIO AO ENSINO DA TEORIA CLÁSSICA DE CONTROLE AUTOMÁTICO - Pereira, Kleber Batistela; Pereira, Wilton Ney do Amaral; Garbi, Giuliani Paulineli (Revista Ciências Exatas, 2012)
The work get the development of the academic controller to a servo machine with the strategics of the Proporcional Integral and Derivative Controller (PID). This works refers too for all analytics concept of engineering of the classic control for the development and application of the controller in a academic kit. The results about the working of controller are demonstrate by simulations in the MatLab software and after that compared the pratical results.